Why People Avoid the News and How (Not) to Combat It - Kazun, Anastasia (Journal of Economic Sociology, 2025)
The reviewed monograph addresses the burgeoning phenomenon of news avoidance, a consequence of information overload, media fragmentation, declining trust in news sources, and the pervasive negativity characterizing contemporary news coverage. Drawing on extensive empirical data, the authors offer a comprehensive examination of the motivations and factors underpinning this trend. Their analysis reveals a higher propensity for news avoidance among women, younger individuals, and those from lower socioeconomic backgrounds. Furthermore, the study highlights the influence of beliefs about news, political affiliations, news socialization experiences, and social norms on news consumption patterns. Individuals who avoid news frequently cite contentrelated deficiencies—excessive negativity, perceived inaccuracy, complexity, and perceived irrelevance to their daily lives—alongside personal characteristics as contributing factors. The review critically assesses the authors’ recommendations for ournalists aiming to counteract news avoidance, questioning their practicality and potential efficacy. The monograph’s call for increased audience engagement in news consumption lacks sufficient justification, while certain proposed strategies are argued to potentially yield counterproductive outcomes. Despite these reservations, the monograph makes a significant contribution to the ongoing scholarly discourse surrounding news avoidance in the contemporary information landscape.